Common injuries among javelin throwers: A 10-year overview (2007-2016) - Duvenage, T.; Ellapen, T. J.; Qumbu, B. T.; Swanepoel, M.; Strydom, G. L. (African Journal for Physical, Health Education, Recreation and Dance, 2017)
The sport of javelin throwing is a popular track and field competition enjoyed by many spectators and athletes and performed at both national and international levels. It has gained popularity in the IAAF (International Association of Athletics Federation) recognised competitions including the Olympic Games. Like athletes in all sports, javelin throwers are prone to injuries. This review was undertaken to provide an overview of the common javelin throwing injuries recorded internationally during 2007 to 2016. A systematic review of literature following the PRIMSA guidelines from 2007 to 2016 was used. Records were appraised according to the modified Downs and Black Appraisal Scale. The literature review identified 1710 English records. After the application of the exclusion criteria, 12 papers were included in the study. Javelin throwers experience a high prevalence of shoulder, elbow, lower back and knee injuries. The most common type of injury was the medial ulnar collateral ligament sprain, commonly known as javelin thrower`s elbow. The primary cause of injuries was poor throwing biomechanics that led to compensatory movement patterns, resulting in synergistic muscle dominance. The need for prospective studies is recommended.